Injectable hydrogel/micro-composite systems for in situ therapeutic cell delivery - Wang, Chunming (2009)
Hydrogels are promising cell delivery vehicles due to their remarkable advantages, especially injectability that enables in situ delivery and localisation. However, expanding applications of hydrogels into wider fields of cell therapeutics has been hurdled by a substantial challenge, that is, anchorage-dependent cells (ADCs) show poor settlement when encapsulated into 3D hydrogel frameworks. Knowledge form cell biology and endeavours made by pioneer researchers suggested that the problem should lie in the absence of ‘adhesive anchors’ for ADCs within hydrogel bulk. Accordingly in this PhD study, such ‘anchors’ were proposed to be set up, with the aim to activate cellular focal adhesion (FA) and promote cell growth within a bioinert hydrogel. Furthermore, these ‘anchors’ were assumed to be at micro-scale, serving as cell-adhesive interface in the aqueous and bio-inert 3D matrices. Based on such hypothesis, a hydrogel / micro-composite systems was devised for delivering ADCs with tissue regenerative prospect with nano-aggregates (in micron-size) or polysaccharide-based microcarriers as the ‘adhesive anchors’. Typical ADC species (and their progenitor cells) such as fibroblasts, osteoblasts and / or mesenchymal stem cells were first cultured on the ‘adhesive anchors’ to evaluate their FA-promoting efficacies. Eventually, the hydrogel / microcarrier composite with ADC-laden microspheres encapsulated inside hydrogel was considered as a competitive platform for ADC delivery, according to its encouraging performance in supporting ADC spreading, proliferation, differentiation, as well as tissue formation in in vivo osteogenic models. Meanwhile, the biochemical mechanisms behind cell survival / death within 3D hydrogels were elicited, which confirmed the necessity of integrin ligation in avoiding apoptosis and promoting differentiation/proliferation of ADC species.